A high-coverage Neandertal genome from the Altai Mountains reveals population structure among Neandertals - Diyendo Massilani; Stéphane Peyrégne; Leonardo N. M. Iasi; Cesare de Filippo; Fabrizio Mafessoni; Alba Bossoms Mesa; Arev P. Sümer; Yaniv Swiel; Divyaratan Popli; Shahar Silverman; Michael James Boyle; Maxim B. Kozlikin; et al. (Proceedings of the National Academy of Sciences, 2026)
We present a genome sequenced to ~37-fold genomic coverage from an approximately 110,000-y-old male Neandertal from Denisova Cave in the Altai Mountains and analyze it together with previously published Neandertal genomes of high quality. We show that he belonged to a population more closely related to a ~120,000-y-old Neandertal from Denisova Cave than to Neandertals in Europe or to a ~80,000-y-old Neandertal from Chagyrskaya Cave in the Altai Mountains. Both Neandertals from Denisova Cave show evidence of gene flow from Denisovans, a pattern not seen in later Neandertals from the Altai region or from Western Europe. The extent of chromosomal regions of homozygosity in Neandertals from the Altai region between 120,000 and 80,000 y ago indicates that they lived in smaller and more isolated groups than later Neandertals in Europe (54,000 to 40,000 y ago). We estimate the extent of allele frequency differentiation among Neandertal populations and find that the older Eastern Neandertals in the Altai region and younger Western Neandertals in Europe were as differentiated as the most differentiated present-day human populations worldwide.